Procedures of Islamic legislation against Domestic violence - Abd, Dr.Mohammed Hashim (Thi Qar Arts Journal, 2024)
Domestic violence is indeed one of the most prevalent issues in contemporary society, and its effects are increasingly visible in reality. It requires immediate action to halt this phenomenon and repair the remaining family values in our society. The problems arise between parents and their children, mothers and their children, or between spouses, with children being the most affected. Domestic violence has negative impacts on social life, leading to aggression and isolation in children, which can result in them developing weak personalities as adults. Similarly, women subjected to violence may suffer the same fate. Islamic law rejects violence in all its forms and calls for a gentle, tolerant, and loving approach, adherence to good manners, and consideration of rights and duties. The law prohibits assault, transgression, cruelty, and injustice against others, especially within the family. Islamic teachings are concerned with these issues. Islamic teachings focus on establishing the ideal family based on love, kindness, and compassion, strengthening the relationship between family members because if the family is righteous, so is the society. However, when domestic violence occurs, it contradicts values, morals, and good customs, leading to tragedies, suffering, family disintegration, and loss of rights. Due to its severe danger to both individuals and society, it remains a social challenge. It is widespread in our current reality and cannot be ignored, lest its effects and damages on the security and safety of families and society increase. Therefore, it is necessary to understand its causes and types and to outline methods of treatment and combat, through the perspective of Islamic law derived from the spirit of the Holy Quran and the noble Sunnah. This highlights the importance of this study.